Peran manajemen strategi dalam mewujudkan visi dan misi Bank Permata - Rahmadana, Muhammad Ilham Putra (Maliki Interdisciplinary Journal, 2024)
This study aims to analyse the role of strategic management in realising Bank Permata's vision and mission, as well as to identify the strengths, weaknesses, opportunities and threats (SWOT) that affect the bank's performance. Bank Permata's vision of becoming a leading and professional financial services provider with close relationships with customers demonstrates the bank's commitment to creating long-term relationships based on trust and customer satisfaction. The bank's mission focuses more on prudent and sustainable business management, as well as providing financial solutions according to customer needs. Through SWOT analysis, it was found that Bank Permata has a strong reputation, extensive network, and commitment to digital innovation, but still faces challenges in market share and NPL ratio. Major opportunities exist in the development of digital banking and the SME market, while threats come from intense competition in the industry and the development of fintech. With careful strategic management, Bank Permata can overcome these challenges and achieve sustainable growth